Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Le pouvoir dans les groupes de femmes de la région de Québec - Couillard, Marie-Andrée (Recherches sociographiques, 1994)
Les idéaux féministes d'égalité formulés au cours des années 1970 et 1980 sont aujourd'hui confrontés à des discours divers qui pénètrent les groupes de femmes. D'une part, la vision des technocrates les incite à accepter des fonctions instrumentales en retour d'un financement considéré essentiel par plusieurs. La majorité des groupes en sont ainsi venus à offrir des services qui se situent dans le prolongement de ceux offerts par le réseau de la santé et des services sociaux. À travers ces ajustements, les groupes de femmes ne se définissent plus seulement comme des lieux de conscientisation et de résistance, mais bien comme des groupes communautaires travaillant, de concert avec d'autres groupes communautaires, à l'amélioration du bien-être collectif. Les discours savants portant sur le féminisme, sur les conditions de sa mise en oeuvre ou sur le rapport entre l'État et le communautaire rejoignent eux aussi les militantes et affectent de façons diverses le portrait qu'elles tracent de leurs pratiques. C'est cet ensemble complexe dans lequel des rapports de force se nouent quotidiennement que nous voulons décrire et analyser ici.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; discipline; groupes de femmes; histoire et politique; militance; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Méthodologie féministe pour les femmes et le développement : concepts, contextes et pratiques dans L'égalité devant soi: sexes, rapports sociaux et développement international - Dagenais, Huguette (L'égalité devant soi: sexes, rapports sociaux et développement international, 1994)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; sexisme; système colonial; systèmes d'oppressions; thématiques

Interventions féministes : parcours et perspectives - De Koninck, Maria; Pâquet-Deehy, Ann; Dennie, Maureen; Savard, Sylvie; Turgeon, Joane (Nouvelles pratiques sociales, 1994)
L'article présente une synthèse des résultats de deux recherches réalisées en concertation et portant sur l'intervention féministe dans les domaines de la santé et des services sociaux au Québec. Recensions d'écrits complétées par une collecte de données auprès d'intervenantes oeuvrant sur le terrain, les recherches ont permis de constater que l'intervention féministe se répand et se diversifie. À partir de ce constat, les auteures proposent des réflexions et soulèvent des questions sur la pertinence, les possibilités et les mécanismes pouvant favoriser la recherche théorique sur la base des pratiques.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; cours; discipline; intervention sociale; périodes historiques; québec; régions géographiques; santé; santé des femmes*; sciences humaines; thématiques; travail social; trs3500

La peur de l'autre en soi: du sexisme à l'homophobie - Dorais, Michel; Dutey, Pierre; Welzer-Lang, Daniel (Collection Des Hommes en changement, 1994)
Qu’est-ce que l’homophobie ? C’est l’appréhension de cette femme qui sommeille en chaque homme, de cet homme qui dort en chaque femme, de cet homosexuel ou cette homosexuelle qui, sait-on jamais, n’attend peut-être qu’à s’éveiller en nous.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Outlaw culture: Resisting representations - hooks, bell (Routledge, 1994)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amériques; approches et analyses; féminismes noirs; périodes historiques; racisme; représentations; représentations médiatiques; régions géographiques; sexisme; systèmes d'oppressions; états-unis

Creating worlds for my music to exist: How women composers of electroacoustic music make place for their voices - McCartney, Andra (Université York, 1994)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
Keywords: 1900-1999; 1990-1999; DIG; amériques; arts; canada; discipline; femmes* artistes; genre; montréal; musique; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; toronto; vancouver

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions